2017
DOI: 10.1016/j.juro.2017.03.077
|View full text |Cite
|
Sign up to set email alerts
|

Routine Ertapenem Prophylaxis for Transrectal Ultrasound Guided Prostate Biopsy does Not Select for Carbapenem Resistant Organisms: A Prospective Cohort Study

Abstract: Single dose ertapenem prophylaxis did not appear to have a significant selective effect on fecal colonization with carbapenem resistant Enterobacteriaceae or other ertapenem resistant gram-negative organisms in this outpatient group. It is highly effective prophylaxis for transrectal ultrasound guided prostate biopsy. In the right setting ertapenem may represent a useful prophylactic option to prevent post-transrectal ultrasound guided prostate biopsy sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 26 publications
4
12
0
Order By: Relevance
“…In the present study, MGN rats showed slightly increased mRNA and protein expression levels of Nrf2 and its targeted genes NQO1 and HO-1 along with decreased mRNA and protein expression levels of Keap1 when compared to controls in kidney. The results are in agreement with the observations made by Sutariya, Saraf43 Additionally, treatment of either ILQ or TCPA-1 to MGN rats significantly upregulated the renal mRNA and protein expression levels of Nrf2 and its targeted genes NQO1 and HO-1 with downregulation in the mRNA and protein expression levels of Keap1 compared with that of MGN control rats. These findings are supported by the recent study which shows ILQ treatment induces the expression of NQO1 and HO-1 through the Keap1–Nrf2 pathway 26.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, MGN rats showed slightly increased mRNA and protein expression levels of Nrf2 and its targeted genes NQO1 and HO-1 along with decreased mRNA and protein expression levels of Keap1 when compared to controls in kidney. The results are in agreement with the observations made by Sutariya, Saraf43 Additionally, treatment of either ILQ or TCPA-1 to MGN rats significantly upregulated the renal mRNA and protein expression levels of Nrf2 and its targeted genes NQO1 and HO-1 with downregulation in the mRNA and protein expression levels of Keap1 compared with that of MGN control rats. These findings are supported by the recent study which shows ILQ treatment induces the expression of NQO1 and HO-1 through the Keap1–Nrf2 pathway 26.…”
Section: Discussionsupporting
confidence: 92%
“…In this context, we confirmed the infection rate of almost zero of recent single‐centre studies [12,24]. Several groups suggested upfront antibiotic augmentation [7,25], even using carbapenem‐based prophylaxis [26,27], to face the alarming worldwide increase of post‐procedural sepsis following TR biopsies [3–6]. Given the global warnings on antibiotic overuse, the TP biopsy infection rate should be regarded as a major reason to prefer the TP over the TR approach.…”
Section: Discussionsupporting
confidence: 80%
“…Overall, Enterobacteriaceae carbapenem resistance was not affected by ertapenem consumption. These results are in accordance with stable CRE colonization rates after patients using ertapenem as surgical prophylaxis 20 .…”
Section: Discussionsupporting
confidence: 85%